Respon Pertumbuhan dan Produksi Bawang Merah (Allium ascalonium L.) Terhadap Pupuk NPK dan Dolomit - Laia, Desmawati; Dewi, Dora Silvia; Oesman, Roswita (JURNAL AGROPLASMA, 2025)
This study was conducted at the experimental field of the Indonesian Community Development University (UPMI), Jalan Balai Desa Pasar 12 Marendal II, Patumbak District, Deli Serdang Regency, Medan. The elevation of the site is approximately 40 metres above sea level. The study was conducted from May to July 2025. The efforts required to meet the production needs of red onions involve enhancing soil productivity by utilising NPK fertiliser and dolomite to achieve maximum red onion production. This study employed a randomised block design (RBD) with two factors: NPK fertiliser and dolomite fertiliser. For precision, the experiment was repeated three times. The first factor was NPK fertiliser (N) with four levels: N0 = Control, N1 = 10 g/polybag, N2 = 20 g/polybag, and N3 = 30 g/plant. The second factor was dolomite (D) with four levels: D0 = Control, D1 = 10 g/polybag, D2 = 20 g/polybag, and D3 = 30 g/polybag. The results of the ANOVA test that showed significant effects were followed up with a 5% DMRT test. The response of NPK fertiliser treatment to plant height at 2 mst was significantly influenced, but at plant height observations of 3 mst, 4 mst, number of leaves, number of tubers per plant, tuber diameter, and tuber weight, there was no significant effect but an increase in each treatment. The best treatment average in this study was N2 = 20 g/plant. In this case, the dose or level of dolomite treatment should be increased further to achieve maximum production. Keywords: shallots, dolomite fertiliser, NPK fertiliser